Protecting your children online what you need to know about online threats to your children - McCabe, Kimberly A. 1965- (Rowman & Littlefield, 2017)
Addresses several types of cyber crimes, ranging from child pornography and solicitation to cyberbullying, cyberstalking, and sexting, giving parents the necessary information they need to protect their children in cyberspace. This book builds on the historical efforts to reduce child abuse in the United States and looks at the limitations of these efforts when attempting to address child abuse in cyberspace. By identifying these different types of cybercrimes against children, and offering the definitions of terms and law enacted to prohibit these crimes, Kimberly McCabe gives possible responses for attempting to end internet crime on a national, international, and personal level.